The prevalence, nature and psychological correlates of bullying in Irish prisons - Leddy, Joanne (Legal and criminological psychology, 2002)
Purpose. The objectives of the study were to analyse the prevalence and nature of bullying reported among a representative sample of prisoners in Irish custodial institutions, to identify potential correlates of bullying behaviour and vulnerability to victimization, and to assess the psychological impact of the experience of bullying. Methods. The sample was selected from seven separate custodial institutions and consisted of 213 male and 19 female inmates. In a structured interview, prisoners were asked to report their experience of bullying and were categorized as ‘pure bullies’, ‘bully-victims’, ‘pure victims’ or ‘not involved’. The General Health Questionnaire (GHQ, short version) was used to assess the psychological well-being of the interviewees. Results. The level of victimization was very high, with almost half of the interviewees reporting at least one type of victimization. Slightly over a quarter reported bullying another inmate, although the majority of these had themselves been victimized. Bullying took many forms but the most common were verbal abuse, theft and assault with and without an implement. Females reported engaging in bullying more frequently than males, especially in less direct forms. Victims (including bully-victims) had significantly higher GHQ scores, indicating greater psychological distress than those not bullied. ‘Pure victims’ were older than other inmates and had entered the prison system at an older age. Conclusion. Definitional differences make cross-national comparisons difficult but bullying in Ireland shows many of the same characteristics as reported in UK studies. The phenomenon of older victims may be a distinctive feature. The category of ‘pure bully’ is a useful one to include in future research.